Adequacy of Magnetic Resonance Image versus Electromyography in Patients with Back Pain - Ahmed Obaid Hossain (Journal of Global Pharma Technology, 2018)
This study included patients with back pain. The electromyography (EMG) test were done in the neurophysiology unit in Mirgan hospital in Babylon city and the magnetic resonance image (MRI) test done in the radiologist unit in Hilla surgical teaching hospital. The important results in this study the distribution of patients with back pain according to EMG 96% of patients diagnosed as lumber radiculopathy while according MRI 98% of patients diagnosed as lumber Radiculopathy. The distribution of patients with lumber radiculopathy according to MRI results including (severity and root affected) the (MRI) more accuracy than (EMG) in diagnosis of back pain and the most lumber radiculo pathy effected in EMG are L4 and L5 while the most lumber radiculopathy effected in MRI areL4 ,L5 and S1.Key words: MRI :( magnetic resonance image),EMG :( electromyography).